2020
DOI: 10.1093/publius/pjaa008
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Policymaking in the States: A View at 2020

Abstract: Climate change policymaking has stalled at the federal level in the United States, especially since Donald Trump’s election as president. Concurrently, extreme weather, rising sea levels, and other climatic effects have increased the salience of climate change in the mass public and among elected officials. In response, legislators in state governments increasingly introduce and adopt policies associated with climate change. In this article, we evaluate the state of climate change policymaking in state legisla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The focus of this paper is on climate mitigation policy, which can take many forms including broad-based climate policies, transportation policies, and electricity sector policies that have climate change implications (Grant et al 2014;Bromley-Trujillo and Holman 2020). In the U.S., states have led in this area since the early 2000s as detailed in scholarly work (e.g., Rabe 2004;Matisoff and Edwards 2014;Bromley-Trujillo and Holman 2020).…”
Section: An Overview Of State Climate Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of this paper is on climate mitigation policy, which can take many forms including broad-based climate policies, transportation policies, and electricity sector policies that have climate change implications (Grant et al 2014;Bromley-Trujillo and Holman 2020). In the U.S., states have led in this area since the early 2000s as detailed in scholarly work (e.g., Rabe 2004;Matisoff and Edwards 2014;Bromley-Trujillo and Holman 2020).…”
Section: An Overview Of State Climate Effortsmentioning
confidence: 99%
“…Democratic control of state governments facilitates climate policy adoption while Republican leadership acts as a veto point for climate legislation, often necessitating a Democrat trifecta to achieve bill passage (Bromley-Trujillo et al 2016;Coley & Hess 2012;Trachtman 2020). There is also evidence to suggest a "counter-partisan response" at the state level (Miras and Rouse 2021); that is, when one party controls the federal government, the opposing party may become emboldened to act at the state-level (Bromley-Trujillo and Holman 2020).…”
Section: Governance and Institutionsmentioning
confidence: 99%
“…As states set targets for green-house gas and CO 2 emissions reductions, policy frameworks and approaches to achieving targets have proliferated. Bromley-Trujillo and Homan thoroughly review state climate change policy making as of 2020, including mitigation and adaptation, and focus particularly on state legislation (Bromley-Trujillo and Holman 2020). Within this broad discussion, they identify two categories of greenhouse gas regulation.…”
Section: Regulations To Reduce Co 2 Emissionsmentioning
confidence: 99%
“…This is true, for example, in the European Union, where subnational goals have emerged alongside the bloc-wide goal of net-zero carbon emissions by 2050 ( 4 ). In the United States, subnational climate commitments have formed in the absence of coordinated federal climate policy ( 5 ). Several US states have taken a wide range of climate actions.…”
mentioning
confidence: 99%
“…To date, states with Democratic governors and state legislative majorities have tended to adopt climate goals and emulate climate policies of states with similar political leadership ( 11 ). However, Bromley-Trujillio et al ( 11 ) found that, as the public becomes more concerned about the dangers posed by climate change, more states begin to respond. When they do so, national and global mitigation frameworks often offer the most robust resources.…”
mentioning
confidence: 99%